Educating the Global Workforce for Public Health - Connie J. Evashwick (Frontiers Research Topics, 2018)
Good quality management of the health system demands a critical mass of health professionals with sound technical knowledge. The education that produces a workforce of appropriate size and skills is often a challenge in the delivery of quality health services. Incidentally, health professionals' education has not kept pace with the new emerging challenges. Recent globalization of health has further led to international migration of health professionals, thereby leading to cross-border recognition of health workers with an appropriate skill-mix, knowledge, and competence. The Lancet Commission Report of 2010 highlighted the need to develop a common strategy at a global level for postgraduate medical, nursing, and public health education that reaches beyond the confines of national borders and the silos of individual professions. This vision would require a series of instructional and institutional reforms, which should be guided by two proposed outcomes: transformative learning and interdependence in education. The purpose of this Research Topic is to increase the shared understanding of the current status of the education of the health workforce around the globe, particularly those working in the public health sector. With this foundation, further research and evaluation studies can then be done with a perspective that addresses global workforce issues impacting access, prevention, and care.